Factors Predicting COVID-19 Vaccine Acceptance among Health Care Workers of Songkhla Hospital - Bumrungsena, Kusak (Princess of Naradhiwas University Journal, 2023)
This research is a cross-sectional analytic study aiming to investigate factors predicting COVID-19 vaccine acceptance among health care workers of Songkhla hospital. Data were collected between February 1st and April 30th, 2021 through questionnaire. The content validity of the IOC for each variable was between 0.6 - 1.0, and Cronbach’s Alpha was 0.85. The data were analyzed by descriptive statistics; number, percentage, mean and standard deviation. The factors predicting COVID-19 vaccine acceptance were analyzed using Stepwise Multivariate linear regression statistics at a confidence level of 0.05. The results showed that among 488 health care workers, only 56.56% had positive opinion towards the vaccine. The predicting factors for accepting the COVID-19 vaccine were seasonal influenza in past years, recommendations from trustworthy persons, having received vaccine without any side effect, Male, office personnel, the risk of contracting COVID-19 while working is reduced, marital status, reduced the new cases. Which can predict 30.00% at p-value = 0.001 Building vaccine acceptance among health care workers should target on those who have not received seasonal influenza vaccination in the past year, or those who had side effect from receiving influenza vaccine, personnel taking care of patients, female, single. In addition, recommendations from trusted persons may help people realize advantages of the vaccine, for example, reducing patients and infection risks.